La inflación en el país y su impacto en la economía de las unidades familiares de la parroquia El Rosario, cantón El Empalme, año 2013 - Vélez España, Karina Lissbeth (2016)
The Rosary is a rural parish in the village of El Empalme, with a population of 9205 inhabitants according to the census conducted by the INEC in 2010. It is located west of Canton and is bordering the province of Manabi through the canton Pichincha who separates a bridge over the river Daule. It sits on an area of 170 km2. Annual inflation in Ecuador in the year 2013 was 2.70% annual average, it may be noted that this was higher in the coastal region in the mountains. Considering the years 2011 and 2012, the indicator is considerably lower. In the first of the mentioned years was 5.41%, while in the second it reached 4.16%. The basket was $ 620.86 in 2013, compared with average monthly household income of US $ 593.60, allowing coverage of the budget by 95.61%, still higher than in 2011 and 2012. He has also been a reduction in the restriction USD -27.26 consumption, which has been beneficial for the economy in general and especially the Rosary parish. The 45.53% of the population surveyed said that two of the family members contribute to household expenses, recording average monthly income in a majority ranging between USD 300 and USD 600. Household consumption in the parish El Rosario is structured as follows and the following parameters in relation to their income: The 34.15% spend between 40% and 60% in power. Another 43.36% consume 10% to 20% on clothing and footwear. 41.19% spend 20% to 30% on housing. A 56.64% invest from 0% to 10% in entertainment and recreation, followed by 42.28% which allocates 10% to 20% in education and health. 95.56% for inflation if you have generated a negative impact on the family economy, which is why the 35.77% seen in the need to reduce staff working in the agricultural, livestock production, finding new forms of negotiation between others, in order to cut costs, to thereby hedge against the price increase.